Suspension Bridge Simulation Modeling in Overcoming Seismic Loads - Pong Krit; Rit Som; Som Chai (Yayasan Adra Karima Hubbi, 2024)
The increasing frequency of seismic events poses significant challenges to the structural integrity of suspension bridges. Understanding how these structures respond to seismic loads is essential for ensuring their safety and performance. Effective modeling and simulation techniques can provide valuable insights into the behavior of suspension bridges under such conditions. This study aims to develop a simulation model for suspension bridges to assess their performance under seismic loading. The research seeks to identify critical factors influencing the bridge's response and propose design modifications to enhance resilience against earthquakes. A finite element analysis (FEA) approach was employed to create a detailed simulation model of a suspension bridge. Various seismic scenarios were simulated using different ground motion records. Key parameters, including displacement, stress, and dynamic response, were monitored and analyzed to evaluate the bridge's behavior. The simulation results indicated that the suspension bridge exhibited significant displacement under seismic loads, particularly at the midspan. Stress concentrations were observed at critical joints and cables, highlighting potential failure points. Design modifications, such as increased cable tension and enhanced damping systems, were proposed to improve the bridge's seismic performance. The research concludes that simulation modeling is a valuable tool for understanding the seismic response of suspension bridges. The findings emphasize the importance of incorporating seismic considerations into the design process. Future research should focus on validating the simulation results with experimental data and exploring advanced materials and technologies to further enhance bridge resilience.